A review of biotechnological approaches towards crop improvement in African yam bean (Sphenostylis stenocarpa Hochst. Ex A. Rich.) - Oluwole, O.O.; Aworunse, O.S.; Aina, A.I.; Oyesola, O.L.; Popoola, J.O.; Oyatomi, Olaniyi; Abberton, Michael T.; Obembe, O. (Elsevier, 2021)
Globally, climate change is a major factor that contributes significantly to food and nutrition insecurity, limiting crop yield and availability. Although efforts are being made to curb food insecurity, millions of people still suffer from malnutrition. For the United Nations (UN) Sustainable Development Goal of Food Security to be achieved, diverse cropping systems must be developed instead of relying mainly on a few staple crops. Many orphan legumes have untapped potential that can be of significance for developing improved cultivars with enhanced tolerance to changing climatic conditions. One typical example of such an orphan crop is Sphenostylis stenocarpa Hochst. Ex A. Rich. Harms, popularly known as African yam bean (AYB). The crop is an underutilised tropical legume that is climate-resilient and has excellent potential for smallholder agriculture in sub-Saharan Africa (SSA). Studies on AYB have featured morphological characterisation, assessment of genetic diversity using various molecular markers, and the development of tissue culture protocols for rapidly multiplying propagules. However, these have not translated into varietal development, and low yields remain a challenge. The application of suitable biotechnologies to improve AYB is imperative for increased yield, sustainable utilisation and conservation. This review discusses biotechnological strategies with prospective applications for AYB improvement. The potential risks of these strategies are also highlighted.